A new freshwater leech species of Helobdella (Annelida: Glossiphoniidae) from central Mexico - Oceguera-Figueroa, Alejandro; Leon-Regagnon, Virginia (Zootaxa, 2005)
Helobdella atli n sp. is described based on the examination of 20 specimens collected in Totolcingo Lake, Tlaxcala, Mexico. Leeches were found attached to submerged rocks and plants. Study of specimens included optical and scanning electron microscopy. Diagnostic characters are: sperm ducts with a long posterior extension, a dorsal nuchal scute on somite VIII, postcaeca absent in the last pair of crop caeca and the mouth pore in the anterior margin of the oral sucker. Previous records of H. adiastola in Mexico correspond to H. atli n. sp.